지역사회 재가 노인의 기능장애 위험요인 - 송현종(Hyun-jong Song) (保健敎育健康增進學會誌, 2015)
Objectives: The purpose of this study was to investigate risk factors for chronic ADL, IADL disability. The study explored clinical and socio-demographic risk factors of functional status decline. Methods: Data from the Survey of Living Condition of Elderly 3-year panel study were analyzed. The study subjects were 5,928 community-dwelling people aged 65 years or older who were no disability in ADL and IADL at baseline. Predisposing factors, pathology, impairment, and functional limitations were regarded as risk factors. Logistic regression analysis was used. Results: During the 3-year study period, 3.9% participants developed chronic ADL disability, 9.4% participants were IADL disabled. After controlling for predisposing factor, the best predictors for ADL disability at 36 months were fall as a pathology factor, cognitive decline, disability judgement, lower limb functional limitation. Comorbidity, fall, cognitive decline, disability judgement, lower limb and upper limb functional limitation were risk factors for IADL disability. Conclusions: Health promotion program focusing elderly is essential to prevent ADL and IADL disability. Mobilizing physical activity should be included in health promotion program for elderly.